They also die, who stand and watch - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Berkeley:::University place::::::::::::
Silk screen print of a standing man and two females on the ground being threatened by an armed guardsman. The words "they also die who stand and watch" are written on the poster as a recollection that innocent bystanders were also killed or injured at demonstrations held on May 4, 1970 at Kent State University and on May 14, 1970 at Jackson State College. At the bottom right of the poster appears the number "4973" which is believed to be a code issued by the Berkeley Police Department clearing the poster from being removed.